2015
DOI: 10.1016/j.nut.2015.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of iron-enriched baker's yeast and its efficiency in recovery of rats from dietary iron deficiency

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…In humans, the capacity of iron absorption from the diet depends on various factors, including the amount of iron in the body, the rate of erythrocyte production, the amount and kind of iron in the diet, and the presence of dietary absorption enhancers and inhibitors. In my previous work we proved that ingestion of iron-enriched yeast is more efficient than inorganic treatment in recovery from iron deficiency, including tissue recovery in rats (Kyyaly et al, 2015). Our recent studies (not published yet) showed that there was no effect of iron salt addition on the production yield when we used molasses growth medium, which is the industrial medium used for baker's yeast production, for production of iron enriched yeast.…”
Section: Introductionmentioning
confidence: 88%
“…In humans, the capacity of iron absorption from the diet depends on various factors, including the amount of iron in the body, the rate of erythrocyte production, the amount and kind of iron in the diet, and the presence of dietary absorption enhancers and inhibitors. In my previous work we proved that ingestion of iron-enriched yeast is more efficient than inorganic treatment in recovery from iron deficiency, including tissue recovery in rats (Kyyaly et al, 2015). Our recent studies (not published yet) showed that there was no effect of iron salt addition on the production yield when we used molasses growth medium, which is the industrial medium used for baker's yeast production, for production of iron enriched yeast.…”
Section: Introductionmentioning
confidence: 88%
“…Many proteins, such as thiolated human-like collagen, can chelate iron, as can the iron metabolism-related proteins [55]. In iron-enriched baker’s yeast and soybeans, iron also binds proteins [53,62]. Some complexes, such as iron-bound whey proteins, have good stability under different processing conditions [56].…”
Section: Iron-chelatable Protein Hydrolysatesmentioning
confidence: 99%
“…Soybean sprouts fortified with iron (ferritin) are a good iron supplement with no side effects [53]. Iron-enriched baker’s yeast, which contains iron bound to proteins in the yeast cells, is more efficient than inorganic iron in treating anaemic rats [62]. …”
Section: Usages Advantages and Challenges Of Protein Hydrolysatesmentioning
confidence: 99%
“…Interestingly, iron-enriched yeasts are currently being evaluated as promising sources of iron to prevent and palliate iron deficiency in humans and animals (1). In fact, recent reports have indicated that iron-enriched baker's yeasts are efficient for helping animals recover from iron deficiency, while maintaining their fermentative and bakery properties (2,3).…”
mentioning
confidence: 99%